The Digital Public Sphere and Muslim Piety in Aceh: Rethinking Habermas Conception of Communicative Action - Bhakti, Sufri Eka; Dhuhri, Saifuddin (Islam Realitas: Journal of Islamic and Social Studies, 2022)
This study offers insights into the transformation of social media platforms as an alternative to the digital public sphere for Muslim society in Aceh. The communicative action theory by Habermas is used as approach to respond to this challenge. Descriptive quantitative analyses were used to expose religious discourse about Islam amongst young Muslims in Aceh. The results show that WhatsApp has proven to be the most popular among social media platforms. WhatsApp has functioned as a new public sphere for Muslim society in Aceh and has evolved into an essential part of mediated Islamic discourse in the digital era. In this regard, WhatsApp has created a universal public sphere, available to Muslim society as dialogic communication in Aceh. This research concludes that the Muslims in Aceh are not merely users of WhatsApp. They can also be digital preachers who can build individual narratives as a part of the religious struggle to increase their piety.Kajian ini dilakukan untuk memberikan pemahaman mendalam tentang bagaimana transformasi platform media sosial sebagai alternatif ruang publik digital pada masyarakat Muslim di Aceh. Teori tindakan komunikatif Habermas digunakan sebagai pendekatan untuk menjawab tantangan ini. Analisis deskriptif kuantitatif digunakan untuk mengekspos diskursus keagamaan Islam di kalangan generasi muda Muslim di Aceh melalui lanskap media sosial baru yang lebih kontemporer. Hasilnya menunjukkan bahwa WhatsApp telah terbukti menjadi media yang paling populer di antara banyak platform media sosial. WhatsApp telah memberikan manfaat sebagai alternatif ruang publik baru bagi masyarakat Muslim di Aceh dan telah berkembang menjadi bagian penting dalam perkembangan diskursus keislaman di era digital. Dalam hal ini, WhatsApp telah menciptakan ruang publik yang universal, tersedia bagi Muslim sebagai satu bentuk komunikasi dialogis di Aceh. Penelitian ini menyimpulkan bahwa umat Islam di Aceh bukan hanya pengguna WhatsApp saja. Namun, mereka juga menjadi penceramah digital yang dapat membangun narasi individu yang dipilih sebagai bagian dari perjuangan dakwah untuk meningkatkan ketakwaannya